A novel ML protein functions as a pattern recognition protein in antibacterial responses in Eriocheir sinensis. (February 2022) - Song, Yu; Zhou, Kaimin; Nan, Xingyu; Qin, Yukai; Zhao, Ke; Li, Weiwei; Wang, Qun
Abstract: The myeloid differentiation factor 2 (MD-2)-related lipid recognition (ML) domain is present in MD-2, MD-1, GM2-activator protein (GM2A) and Niemann-Pick disease type C2 (NPC2). ML proteins function in antibacterial signal transduction and lipid metabolism in vertebrates, but the mechanism in invertebrates is unknown. In this study, we found that ML proteins were involved in bacterial resistance in Chinese mitten crab ( Eriocheir sinensis ). One member, Es ML3, a soluble, bacterial-induced pattern recognition protein was upregulated in hemocytes following bacterial challenge. Recombinant Es ML3 bound to Gram-negative bacteria ( Vibrio parahaemolyticus ) and Gram-positive bacteria ( Staphylococcus aureus ) by interaction with peptidoglycan, lipopolysaccharide. Es ML3 showed no direct bacteriostatic or bacteriocidal activity. Pre-incubating bacteria with r Es ML3 significantly promoted in vivo bacterial clearance. Es ML3 also promoted phagocytic activity and plays a role against bacterial infection. In summary, Es ML3 mediates cellular immune responses by recognising invasive microorganisms, promoting bacterial clearance and phagocytosis against bacterial infection in crab. Highlight: Es ML3 may function as a pattern recognition protein in crab antibacterial immunity. Es ML3 is upregulated in crab challenged by bacteria. Es ML3 promotes in vivo bacterial clearance and phagocytosis against bacterial infection in crab.